Flow Index accurately identifies breaths with low or high inspiratory effort during pressure support ventilation - Filippo Albani; Federica Fusina; Gianni Ciabatti; Luigi Pisani; Valeria Lippolis; Maria Elena Franceschetti; Alessia Giovannini; Rossella di Mussi; Francesco Murgolo; Antonio Rosano; Salvatore Grasso; Giuseppe Natalini (Critical Care, 2021)
Abstract Background Flow Index, a numerical expression of the shape of the inspiratory flow-time waveform recorded during pressure support ventilation, is associated with patient inspiratory effort. The aim of this study was to assess the accuracy of Flow Index in detecting high or low inspiratory effort during pressure support ventilation and to establish cutoff values for the Flow index to identify these conditions. The secondary aim was to compare the performance of Flow index,of breathing pattern parameters and of airway occlusion pressure (P 0.1) in detecting high or low inspiratory effort during pressure support ventilation. Methods Data from 24 subjects was included in the analysis, accounting for a total of 702 breaths. Breaths with high inspiratory effort were defined by a pressure developed by inspiratory muscles (P musc) greater than 10 cmH2O while breaths with low inspiratory effort were defined by a P musc lower than 5 cmH2O. The areas under the receiver operating characteristic curves of Flow Index and respiratory rate, tidal volume,respiratory rate over tidal volume and P 0.1 were analyzed and compared to identify breaths with low or high inspiratory effort. Results P musc, P 0.1, Pressure Time Product and Flow Index differed between breaths with high, low and intermediate inspiratory effort, while RR, RR/V T and V T/kg of IBW did not differ in a statistically significant way. A Flow index higher than 4.5 identified breaths with high inspiratory effort [AUC 0.89 (CI 95% 0.85–0.93)], a Flow Index lower than 2.6 identified breaths with low inspiratory effort [AUC 0.80 (CI 95% 0.76–0.83)]. Conclusions Flow Index is accurate in detecting high and low spontaneous inspiratory effort during pressure support ventilation.